PEMBUATAN PUPUK ORGANIK PADAT BERBASIS KULIT DURIAN DAN STARDEC DENGAN METODE COMPOSTING AEROB - Suprihatin; Radithya Bagus Sulistya; Jevanya Nathanael Silalahi (Fakultas Teknik Universitas Wahid Hasyim, 2025)
This study aims to examine the effects of Stardec bioactivator dosage and composting time on the nutrient quality of solid organic fertilizer derived from durian peel waste. The method employed was aerobic composting using an in-vessel system with variations in Stardec dosage and composting duration. The results showed that increasing the Stardec dosage and composting period significantly enhanced the macronutrient content. The optimal condition was achieved by adding 15 grams of Stardec on the 15th day, resulting in organic carbon of 26.29%, total nitrogen of 4.76%, total phosphorus (P-total) of 3.97%, and total potassium (K-total) of 4.43%. The resulting C/N ratio ranged between 5–10, indicating good compost maturity and readiness for soil application. All final parameters, including pH and moisture content, complied with the quality standards of SNI 7763-2024, confirming that the product is suitable for use as a safe and nutrient-rich organic fertilizer for soil improvement.